East Asian Arch Psychiatry 2020
DOI: 10.12809/eaap1921
|View full text |Cite
|
Sign up to set email alerts
|

Emotional/Behavioural Problems and Functional Impairment in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Objective: This study aimed to compare the emotional/behavioural problems and functional impairment between early school-age children with attention-deficit/hyperactivity disorder (ADHD) and non-ADHD controls. Factors associated with behavioural problem scores were also evaluated. Methods: Children aged 6 to 10 years who were diagnosed with ADHD based on the Swanson, Nolan and Pelham version IV Scale (SNAP-IV) and the DSM-5 criteria for ADHD were compared with ageand sex-matched controls with negative SNAP-IV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…With a global prevalence of 5.29 to 7.2%, attention-deficit/ hyperactivity disorder (ADHD) is the most common neurodevelopmental psychiatric disorder in childhood and generally persists into adulthood (1). ADHD is generally characterized by developmentally inappropriate levels of "core symptoms, " including inattention, hyperactivity and impulsivity (2), which affect children's behavior, emotion, and executive functions (EFs) and may lead to multidimensional difficulties in their academic and social abilities (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…With a global prevalence of 5.29 to 7.2%, attention-deficit/ hyperactivity disorder (ADHD) is the most common neurodevelopmental psychiatric disorder in childhood and generally persists into adulthood (1). ADHD is generally characterized by developmentally inappropriate levels of "core symptoms, " including inattention, hyperactivity and impulsivity (2), which affect children's behavior, emotion, and executive functions (EFs) and may lead to multidimensional difficulties in their academic and social abilities (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Paap et al [25] found a relationship between peer problems and prosocial behaviour in typically developing 7-9 years old children, but ADHD and ODD act as moderator variables, weakening this relationship. Tengsijaritkul and their colleagues [26] examined functional impairments in treated ADHD children and found that they have lower prosocial scores; moreover, their comorbid medical disorders were associated with higher problem scores. Furthermore, in a clinical study, peer problems and prosocial behaviour of methylphenidate treated children with ADHD and children without ADHD were compared [27].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the assessment of prosocial skills and prosocial behavior in treatment naïve children with ADHD can serve as a baseline measurement for monitoring the efficacy of therapies. Although several previous studies have examined the functional impairment in children with ADHD, including such aspects as social functions, peer functioning and prosocial behaviour, the effectiveness of treatment in clinical trials is not filtered out, which is important when we want to evaluate functional impairment [26][27][28]. To our knowledge, there has not been any research conducted which explored prosocial behaviour and peer relationships among treatment naïve children with ADHD, nor are we aware of any research that explored the relationship between prosocial behaviour, peer relationships and quality of life.…”
Section: Introductionmentioning
confidence: 99%